2014
DOI: 10.1364/boe.5.003376
|View full text |Cite
|
Sign up to set email alerts
|

Sub-diffusive scattering parameter maps recovered using wide-field high-frequency structured light imaging

Abstract: This study investigates the hypothesis that structured light reflectance imaging with high spatial frequency patterns [Formula: see text] can be used to quantitatively map the anisotropic scattering phase function distribution [Formula: see text] in turbid media. Monte Carlo simulations were used in part to establish a semi-empirical model of demodulated reflectance ([Formula: see text]) in terms of dimensionless scattering [Formula: see text] and [Formula: see text], a metric of the first two moments of the [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
86
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 74 publications
(87 citation statements)
references
References 50 publications
0
86
0
Order By: Relevance
“…[7][8][9][10] However, recent work showed that a range of γ values (for the same μ 0 s , μ a , and d det ) can result in the same reflectance.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] However, recent work showed that a range of γ values (for the same μ 0 s , μ a , and d det ) can result in the same reflectance.…”
Section: Introductionmentioning
confidence: 99%
“…3 and 4, the RRE significantly depends on the numerical sampling method and underlying lookup table size. This suggests that special care should be taken when implementing the phase functions in the MC simulations, and moreover, include the information in research articles as this was not a common practice to date [4][5][6][7]10,11].…”
Section: Discussionmentioning
confidence: 99%
“…The anisotropy factor g can be found to be as low as 0.4 [24] and can reach values of up to 0.98 [25] in the biological tissues. With respect to parameter γ, the values tend to lie between 1.1 and 2.3 [6,26,27]. As a result, we have utilized 15 phase functions listed in Table 1.…”
Section: Phase Functions Utilized For Evaluating the Numerical Samplimentioning
confidence: 99%
See 2 more Smart Citations